Sex differences in outcome after thrombectomy for acute ischemic stroke. A propensity score-matched study. (June 2022) - Casetta, Ilaria; Fainardi, Enrico; Pracucci, Giovanni; Saia, Valentina; Sallustio, Fabrizio; da Ros, Valerio; Nappini, Sergio; Nencini, Patrizia; Bigliardi, Guido; Vinci, Sergio; Grillo, Francesco; Bracco, Sandra; et al.
Background and purpose: We sought to investigate whether there are gender differences in clinical outcome after stroke due to large vessel occlusion (LVO) after mechanical thrombectomy (EVT) in a large population of real-world patients. Methods: From the Italian Registry of Endovascular Thrombectomy, we extracted clinical and outcome data of patients treated for stroke due to large vessel occlusion. We compared clinical and safety outcomes in men and women who underwent EVT alone or in combination with intravenous thrombolysis (IVT) in the total population and in a Propensity Score matched set. Results: Among 3422 patients included in the study, 1801 (52.6%) were women. Despite older age at onset (mean 72.4 vs 68.7; p < 0.001), and higher rate of atrial fibrillation (41.7% vs 28.6%; p < 0.001), women had higher probability of 3-month functional independence (adjusted odds ratio-adjOR 1.19; 95% CI 1.02–1.38), of complete recanalization (adjOR 1.25; 95% CI 1.09–1.44) and lower probability of death (adjOR 0.75; 95% CI 0.62–0.90). After propensity-score matching, a well-balanced cohort comprising 1150 men and 1150 women was analyzed, confirming the same results regarding functional outcome (3-month functional independence: OR 1.25; 95% CI 1.04–1.51), and complete recanalization (OR 1.29; 95% CI 1.09–1.53). Conclusions: Subject to the limitations of a non-randomized comparison, women with stroke due to LVO treated with mechanical thrombectomy had a better chance to achieve complete recanalization, and 3-month functional independence than men. The results could be driven by women who underwent combined treatment. Graphical abstract